The Grog Mob: lessons from an evaluation of a multi‐disciplinary alcohol intervention for Aboriginal clients. (1st October 2013) - d'Abbs, Peter; Togni, Samantha; Rosewarne, Clive; Boffa, John
Abstract Objectives: To evaluate a 12‐month trial of an evidence‐based non‐residential treatment program for Indigenous clients with alcohol problems, offering three streams of care: pharmacotherapy, psychological and social support. Methods: Process evaluation of program implementation; outcome evaluation of client outcomes. Results: Implementation: despite constraints of time and remoteness, the trial demonstrated the feasibility of implementing such a program. The medical stream generated fewer pharmacotherapy prescriptions than expected. The most active stream was the psychological therapy stream. Outcomes: between March 2008 and April 2009, 129 clients were referred to the program, of whom 49 consented to have de‐identified data used for the evaluation. Of these, 19 clients received one or more streams of care, 15 of whom (78.9%) subsequently stopped or reduced drinking. However, among the remaining 30 consenting clients who had not received an intervention, 70.0% also reported stopping or reducing drinking. The evidence of program effectiveness is therefore equivocal and evaluation over a longer period is required. Conclusion and implications: The trial demonstrated the viability of, and demand for, evidence‐based non‐residential treatment for Indigenous clients with alcohol problems. Reasons behind an apparent reluctance among GPs to prescribe pharmacotherapy for Indigenous clients, and steps to overcome this, need further attention.